A critical examination of representations of context within research on population health interventions. Issue 5 (19th October 2016) - Shoveller, Jean; Viehbeck, Sarah; Di Ruggiero, Erica; Greyson, Devon; Thomson, Kim; Knight, Rodney
Abstract: Research that fulsomely characterizes context improves our understanding of the processes of implementation and the effectiveness of interventions to improve the health of populations and reduce health inequalities. Context could be a key aspect to understanding what population health interventions best address underlying conditions that contribute to systematic differences in health status at the population level. Here, we present a 'snapshot' of representations of context in population health intervention research published recently in some influential journals in the field of public health. In general, we found that context was treated as a 'black box', or as something that needs to be 'controlled for'. Context also was used to help explain intervention 'failure'. There were few in-depth descriptions of the hypothesized pathways or mechanisms through which context and intervention (in combination or separately) influence population health. Recognizing that research on population health interventions can be less straightforward than research conducted under more 'controlled' (i.e. de-contextualized) conditions, we suggest that there is a great need for new theoretical and methodological work in this area.